Fibrillar vs crystalline nanocellulose pulmonary epithelial cell responses: Cytotoxicity or inflammation? - Menas, Autumn L.; Yanamala, Naveena; Farcas, Mariana T.; Russo, Maria; Friend, Sherri; Fournier, Philip M.; Star, Alexander; Iavicoli, Ivo; Shurin, Galina V.; Vogel, Ulla B.; Fadeel, Bengt; Beezhold, Donald; et al. (Chemosphere (Oxford), 2017)
Nanocellulose (NC) is emerging as a highly promising nanomaterial for a wide range of applications. Moreover, many types of NC are produced, each exhibiting a slightly different shape, size, and chemistry. The main objective of this study was to compare cytotoxic effects of cellulose nanocrystals (CNC) and nanofibrillated cellulose (NCF). The human lung epithelial cells (A549) were exposed for 24 h and 72 h to five different NC particles to determine how variations in properties contribute to cellular outcomes, including cytotoxicity, oxidative stress, and cytokine secretion. Our results showed that NCF were more toxic compared to CNC particles with respect to cytotoxicity and oxidative stress responses. However, exposure to CNC caused an inflammatory response with significantly elevated inflammatory cytokines/chemokines compared to NCF. Interestingly, cellulose staining indicated that CNC particles, but not NCF, were taken up by the cells. Furthermore, clustering analysis of the inflammatory cytokines revealed a similarity of NCF to the carbon nanofibers response and CNC to the chitin, a known immune modulator and innate cell activator. Taken together, the present study has revealed distinct differences between fibrillar and crystalline nanocellulose and demonstrated that physicochemical properties of NC are critical in determining their toxicity. [Display omitted] •Biological Responses of NC are orchestrated by their dimensions and morphology.•NCF cytotoxicity may be caused by oxidative stress and not cellular uptake.•Viability and oxidative damage models may not be effective in predicting toxicity.•NC with different morphologies revealed drastic changes in the cytokine profiles.•Exposure to various NC revealed distinct cytotoxic responses and cytokine signatures.